2015
DOI: 10.2139/ssrn.2620229
|View full text |Cite
|
Sign up to set email alerts
|

What Do We Learn from Public Good Games About Voluntary Climate Action? Evidence from an Artefactual Field Experiment

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 72 publications
(98 reference statements)
0
5
0
Order By: Relevance
“…Similarly, we can wonder about the external validity of the PSB measure, and whether the prisoner’s dilemma game is useful in thinking about real world situations. Note that different studies have corroborated the external validity of the public good games ( Franzen and Pointner, 2013 ; Stoop, 2014 ; Goeschl et al, 2015 ; Rommel et al, 2015 ). In a recent study, Franzen and Pointner (2013) have demonstrated that in lab behavior is related to PSB in the field—these authors used a measure of PSB with a dilemma game similar to the one we have used in this experiment.…”
Section: General Discussion and Concluding Remarksmentioning
confidence: 90%
See 1 more Smart Citation
“…Similarly, we can wonder about the external validity of the PSB measure, and whether the prisoner’s dilemma game is useful in thinking about real world situations. Note that different studies have corroborated the external validity of the public good games ( Franzen and Pointner, 2013 ; Stoop, 2014 ; Goeschl et al, 2015 ; Rommel et al, 2015 ). In a recent study, Franzen and Pointner (2013) have demonstrated that in lab behavior is related to PSB in the field—these authors used a measure of PSB with a dilemma game similar to the one we have used in this experiment.…”
Section: General Discussion and Concluding Remarksmentioning
confidence: 90%
“…In a recent study, Franzen and Pointner (2013) have demonstrated that in lab behavior is related to PSB in the field—these authors used a measure of PSB with a dilemma game similar to the one we have used in this experiment. Moreover, recently Goeschl et al (2015) have shown that the prisoner’s dilemma game is related to PSB (giving money to reduce CO 2 emissions) in the field. Thus, research is showing some evidences of external validity of the prisoner’s dilemma game, and there is no reason to believe that the measure used in this experiment to assess PSB (the prisoner’s dilemma game) does not have ecological validity.…”
Section: General Discussion and Concluding Remarksmentioning
confidence: 99%
“…The research assistant made sure that none of the subjects had previous experience with 8 The procedure, as well as a translation of the z-Tree instructions are provided in the Appendix. 9 Total earnings and duration for Experiment 1 encompass a second task (public goods game) that we analyse in a separate paper [35] and that took place subsequent to any decisions analysed in this paper. economic experiments or had taken part in a previous session.…”
Section: Methodsmentioning
confidence: 99%
“…Though other aspects of context (broadly defined) have been studied—including different incentives (e.g., Englmaier and Gebhardt 2016), different parameters and group sizes (e.g., Goeschl et al. 2015), and valence framing effects—here I focus on contextual framing effects (Figure 2 and Table S4). Hagen and Hammerstein (2006, 345) define a frame as “a knowledge structure or conceptual abstraction used to interpret a complex reality or experience, and guide behavior.” Even though classical EEGs are intentionally abstract and devoid of context, participants may provide their own frame by invoking relational cues, social and cultural norms, decision‐making heuristics, and past experiences.…”
Section: Generalizabilitymentioning
confidence: 99%
“…One final aspect of generalizability that is often perceived as a threat to the external validity of EEGs is the sensitivity of game behavior to subtle changes in the contextual framing of the game (Levitt and List 2007a). Though other aspects of context (broadly defined) have been studied-including different incentives (e.g., Englmaier and Gebhardt 2016), different parameters and group sizes (e.g., Goeschl et al 2015), and valence framing effects-here I focus on contextual framing effects (Figure 2 and Table S4). Hagen and Hammerstein (2006, 345) define a frame as "a knowledge structure or conceptual abstraction used to interpret a complex reality or experience, and guide behavior."…”
Section: Across Contextual Framesmentioning
confidence: 99%